The law of occupiers liability in Malaysia a comparative study with New Zealand, United Kingdom and Australia / Farah Nazriah Mohd Chun Lee...[et al.] - Mohd Chun Lee, Farah Nazriah; Jamaluddin, Fatin Nasihah; Nubli, Natra Adibah; Ismail, Putri Azureen Rais (Faculty of Law, 2014)
The principle of this study is to analyze the law of Occupiers' liability in Malaysia. Currently, Malaysia does not have their own Act regarding the law of Occupiers' liability as we adopted the Common Law principle of Occupiers' liability. This research paper will focus on the current state of law of occupiers' liability in Malaysia, in comparison to other Commonwealth countries that are equipped with their very own Occupiers Liability Act such as New Zealand, United Kingdom, and Australia. In addition, we will lay down the strengths and weaknesses of the Occupiers Liability Act of these three countries. At the end of the paper, we will also provide some recommendation so that it will act as a guideline to the law makers in enacting a specific statute relating to occupiers' liability